Preventing Human Trafficking In Indonesia: The Role Of Legal Empowerment Programs - Moh. Zakky AS; Merita Mece; Hamdan Zoelva; Mohammad Taufik Makarao (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
Trafficking in persons or human trafficking, especially women and children, must be eradicated because it violates human dignity and human rights. This article examines and explores the root causes of human trafficking, the criminal sanctions, and the decisions of judges/trials on trafficking in persons in Indonesia to prevent trafficking in persons through legal empowerment. It is based on normative legal research, that is, legal research conducted by examining literature or secondary data. The study reveals that there are at least 10 (ten) root causes of trafficking in persons, which occur in various places in the world, including in Indonesia, namely poverty, lack or low level of education, demand for cheap labor/demand for sex, lack of the implementation of the human rights laws for vulnerable groups, lack of legitimate economic opportunities, Social factors and cultural practices, conflict and natural disaster, trafficking market as a business that generates a large profit, lack of safe migration options, traffickers. There are criminal sanctions against trafficking in persons in Indonesian legislation. This article highlights the importance of the use of legal empowerment in Indonesia to prevent trafficking in persons and address its root causes.